Effects of radiation on the uncertainty of flame speed determination using spherically propagating flames with CO/CO2/H2O dilutions at elevated pressures. (July 2015) - Sohn, Chae Hoon; Chen, Zheng; Ju, Yiguang
Abstract: This work investigates numerically the effects of spectral dependent radiation on laminar flame speed determination using spherically propagating CH4 /air and H2 /air flames with CO/CO2 /H2 O dilutions at elevated pressures. Three different models, adiabatic, optically thin radiation, and fitted statistically narrow band correlated k (FSNB-CK) models, are employed. The effects of radiation-induced negative burned gas velocity, increased density ratio, and chamber confinement induced flow compression are investigated. It is found that compared to the FSNB-CK model, the adiabatic flame model over-predicts the flame speed by 7% and the optically thin model makes more significant under-prediction. Moreover, this discrepancy increases with pressure. The results also show that a large negative velocity in the burned gas is induced by radiative heat loss and magnified further by the flow compression in a small combustion chamber. The radiation-induced negative burned gas velocity causes an under-estimation of flame speed. Moreover, radiation also increases the density ratio between the burned and the unburned gases. The use of the density ratio of adiabatic flame also causes under-prediction of flame speed. Two radiation corrections taking into account of the negative burned gas velocity and the increased density ratio are recommended for flame speed determination using propagating spherical flame for radiative mixtures. The corrections proposed in this study reduce the uncertainty of flame speed due to radiation.